Postnatal Hyperoxia Exposure Differentially Affects Hepatocytes and Liver Haemopoietic Cells in Newborn Rats - Marconi, Guya Diletta (Public Library of Science, 2014)
Premature newborns are frequently exposed to hyperoxic conditions and experimental data indicate modulation of liver metabolism by hyperoxia in the first postnatal period. Conversely, nothing is known about possible modulation of growth factors and signaling molecules involved in other hyperoxic responses and no data are available about the effects of hyperoxia in postnatal liver haematopoiesis. The aim of the study was to analyse the effects of hyperoxia in the liver tissue (hepatocytes and haemopoietic cells) and to investigate possible changes in the expression of Vascular Endothelial Growth Factor (VEGF), Matrix Metalloproteinase 9 (MMP-9), Hypoxia-Inducible Factor-1α (HIF-1α), endothelial Nitric Oxide Synthase (eNOS), and Nuclear Factor-kB (NF-kB). Experimental design of the study involved exposure of newborn rats to room air (controls), 60% O(2) (moderate hyperoxia), or 95% O(2) (severe hyperoxia) for the first two postnatal weeks. Immunohistochemical and Western blot analyses were performed. Severe hyperoxia increased hepatocyte apoptosis and MMP-9 expression and decreased VEGF expression. Reduced content in reticular fibers was found in moderate and severe hyperoxia. Some other changes were specifically produced in hepatocytes by moderate hyperoxia, i.e., upregulation of HIF-1α and downregulation of eNOS and NF-kB. Postnatal severe hyperoxia exposure increased liver haemopoiesis and upregulated the expression of VEGF (both moderate and severe hyperoxia) and eNOS (severe hyperoxia) in haemopoietic cells. In conclusion, our study showed different effects of hyperoxia on hepatocytes and haemopoietic cells and differential involvement of the above factors. The involvement of VEGF and eNOS in the liver haemopoietic response to hyperoxia may be hypothesized.